P468Pre-diabetes a new risk factor for stroke in non-valvular atrial fibrillation. (18th June 2020) - Kezerle, L; Tsadok, M A; Akriv, A; Feldman, B; Leventer-Roberts, M; Ohana, R; Haim, M
Abstract: Funding Acknowledgements: Pfizer Israel Background: Diabetes mellitus is a well-established independent risk factor for embolic complications in patients with non-valvular atrial fibrillation (NVAF). The association between prediabetes and risk of ischemic stroke, however, has not been studied separately in patients with NVAF. Purpose: To evaluate whether pre-diabetes is associated with increased risk of stroke and death in patients with NVAF Methods: We conducted a prospective, historical cohort study using the Clalit Health Services (CHS) electronic medical records database. The study population included all CHS members ≥ 21 years old, with a first diagnosis of NVAF between January 1 2010 to December 31 2016 and a minimal follow-up period of 1 year. We compared three groups of patients: prediabetes, those with established DM, and normoglycemic individuals Results: A total of 44, 451 cases were identified. The median age was 75 years and 52.5% were women. During a mean follow up of 38 months, the incidence of stroke per 100 person-years in the three study groups was: 1.14 in non-diabetics, 1.40 in pre-diabetics and 2.15 in diabetics. In both univariate and multivariate analyses, pre-diabetes was associated with an increased risk of stroke compared with non-diabetics (Adjusted Hazard Ratio (HR) = 1.19 95% CI 1.01-1.4) even after adjusting for CHA2DS2-VASC individual risk factors and use of oral anti-coagulants while diabetes conferred an even higher risk (vs non-diabetics HR = 1.56, 95% CI ;1.37 - 1.79). The risk for mortality was higher for diabetics (HR =1.47, 95% CI ;1.41, 1.54